IMPLEMENTASI METODE FUZZY INFERENCE SYSTEM TSUKAMOTO DALAM MENENTUKAN PENEMPATAN BIDAN PEGAWAI TIDAK TETAP - Septilia Arfida; Abdillah Kusuma (Jurnal Informatika, 2017)
Fuzzy logic is one method to perform system analysis that contains uncertainty. Fuzzy logic mimics a human mindset called reason, where reason can explain and identify things automatically. This research uses the method of inference of Fuzzy Tsukamoto system in determining the placement of midwife of the non permanent employee. Where to get the output is done stages The establishment of the Fuzzy set, Application function implication, Composition rule, and affirmation (Defuzzyfikasi). A non-permanent midwife is a midwife who is not a civil servant, appointed by an authorized official to carry out the task in the course of implementing a government program. Software development method in this application using Waterfall method with the stages of planning, analysis, design, implementation, and maintenance. This application aims to assist the Dinas Kesehatan in selecting prospective midwives of nonpermanent employees. The result of the implementation of the Fuzzy method in this application is to display the output of the employee midwife is not fixed in accordance with the predefined criteria.Keywords: Implementation, Fuzzy Tsukamoto, Non-Permanent Employee Midwife